A novel method for isolation and recovery of ceramic nanoparticles and metal wear debris from serum lubricants at ultra-low wear rates. (15th September 2016) - Lal, S.; Hall, R.M.; Tipper, J.L.
Graphical abstract: Abstract: Ceramics have been used to deliver significant improvements in the wear properties of orthopaedic bearing materials, which has made it challenging to isolate wear debris from simulator lubricants. Ceramics such as silicon nitride, as well as ceramic-like surface coatings on metal substrates have been explored as potential alternatives to conventional implant materials. Current isolation methods were designed for isolating conventional metal, UHMWPE and ceramic wear debris. In this paper, we describe a methodology for isolation and recovery of ceramic or ceramic-like coating particles and metal wear particles from serum lubricants under ultra-low and low wear performance. Enzymatic digestion was used to digest the serum proteins and sodium polytungstate was used as a novel density gradient medium to isolate particles from proteins and other contaminants by ultracentrifugation. This method demonstrated over 80% recovery of particles and did not alter the size or morphology of ceramic and metal particles during the isolation process. Statement of Significance: Improvements in resistance to wear and mechanical damage of the articulating surfaces have a large influence on longevity and reliability of joint replacement devices. Modern ceramics have demonstrated ultra-low wear rates for hard-on-hard total hip replacements. Generation of very low concentrations of wear debris in simulator lubricants has made it challenging to isolate the particles for characterisation and further analysis. We have introduced a novel method to isolate ceramic and metal particles from serum-based lubricants using enzymatic digestion and novel sodium polytungstate gradients. This is the first study to demonstrate the recovery of ceramic and metal particles from serum lubricants at lowest detectable in vitro wear rates reported in literature.